Spectral analysis of heart rate variability during exercise in trained subjects - Pichon, A. P.; de Bisschop, C.; Roulaud, M.; Denjean, A.; Papelier, Y. (Medicine & Science in Sports & Exercise, 2004)
Purpose: To investigate the effects of strenuous exercise on heart rate variability (HRV). Methods: We evaluated the effects of exercise intensity and duration on HRV indices in 14 healthy trained subjects. Each subject exercised for 3, 6, and 9 min at 60 and 70% of the power achieved at maximal oxygen consumption (PVO2max) and for 3 and 6 min (or 3 min twice) at 80% of PVO2max. The electrocardiogram RR intervals were recorded then processed by fast (FFT) and short-time (STFT) Fourier transform for determination of low-frequency (LF, 0.045-0.15 Hz) and high-frequency (HF, 0.15-1.0 Hz) components. Results: The LF and HF components expressed as absolute power (ms2) decreased significantly at the onset of exercise (P < 0.05). However, with increasing exercise intensity, the HF component expressed as normalized units (n.u.) (reflecting parasympathetic modulation) increased significantly, whereas the LF component (n.u.) and LF/HF ratio (both reflecting sympathetic modulation) decreased significantly (P < 0.05). STFT showed that increasing exercise intensity was associated with a shift in HF peak frequency related to an increase in respiratory rate and a marked decrease in LF power (ms2). Moreover, HFn.u. rose (r = 0.918, P < 0.01) and LFms2 fell as minute ventilation increased (r = 0.906, P < 0.01). Conclusions: Parasympathetic respiratory control and nonautonomic mechanisms may influence the HF-peak shift during strenuous exercise. HRV and the usual indexes of sympathetic activity do not accurately reflect changes in autonomic modulation during exhaustive exercise.